Manajemen Pengembangan Profesionalisme Guru Dalam Meningkatkan Vokasional Anak Tunagrahita Jenjang SMALB Di SLB Negeri Pembina Yogyakarta - Marietta Waluyati; Imam Ghozali (Media Manajemen Pendidikan, 2023)
he purpose of this study was to explore management that is devoted to developing teacher professionalism in an effort to improve the vocational skills of mentally retarded children at the Special High School (SMALB) level at the Pembina State Special School in Yogyakarta. This study uses a qualitative approach with descriptive qualitative type on the grounds that the researcher views that to realize the objectives of this research the most appropriate is to use descriptive qualitative research. The subjects of this study were school principals and teachers at SLB Pembina Yogyakarta. Data collection techniques using observation, interviews, and documentation. To perform data analysis using the Miles and Huberman model with the steps of data collection, data condensation, data presentation, and drawing conclusions. Checking the validity of the data is by increasing persistence and using triangulation of sources and data collection techniques. The results showed that the Yogyakarta Pembina Special School had carried out management functions well through planning, organizing, implementing and controlling. This can be seen from the management process of teacher professionalism development which is carried out well by the Yogyakarta Pembina Special School.